Perancangan Dashboard Untuk Manajemen Penjualan Produk Pada PT. Nutragen Global Esana - tania evrita; Tony Tony (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
PT. Nutragen Global Esana is a manufacturing company that produces Fastbite, Isizoup and Proffle products. Nutagen does not yet have data visualization for monitoring company sales. Therefore, implementing dashboards is necessary to optimize production productivity. The existence of a dashboard can help companies to obtain accurate sales information and can be used to observe business developments in accordance with predetermined targets. The method that will be used in designing the dashboard of Nutragen is the Prototyping method. Tools for data visualization on Nutragen is Power BI, while the data to be used is the sales database for three products produced by Nutragen, namely Fastbite, Isizoup and Proffle products in 2022. The Nutragen product sales dashboard can be used to visualize the distribution of resellers, see the percentage of product sales based on flavor variants, see product sales best selling based on product type and variant, as well as a comparison of payments that are most used and see total product sales per month. The benefit of making this dashboard is that it makes it easier for companies to determine strategies and policies based on the information displayed on the dashboard and makes it easier to monitor product transactions more efficiently.